Gender Mainstreaming or Lyčių Dėmens Integravimo Strategija? A Puzzle of the Adaptation of the Imported Scientific Terms into Lithuanian Language - Žvinklienė, Alina (Sociologija. Mintis ir veiksmas, 2004)
The article is devoted to encourage a scientific discussion about using the both terms lytis -sex and gender in Lithuanian academic language or at least to pay more attention to that issue. A present translation of both terms into only lytis-sex often leads up to misrepresenting the meanings of the original terms. It is argued that distinction between both terms lytis -sex and gender in women’s and gender studies, and attention to the history of the term gender helps the most adequate in meaning translation of English political and scientific phraseology into Lithuanian language. Gender mainstreaming as a case study of the problems of the translation into Lithuanian language is presented.
Keywords: Lithuanian language; concepts; sex and gender